2013
DOI: 10.3109/13816810.2013.838274
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Matrix Metalloproteinases Polymorphisms in Age-Related Macular Degeneration

Abstract: Only MMP-9 Rs3918242 (C->T) single nucleotide polymorphism was found to play a significant role in the development of AMD, and the effect was more pronounced at the age of less than 65 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 28 publications
0
30
0
3
Order By: Relevance
“…To our knowledge, there is only one study analyzing the impact of MMP-2, MMP-3, and MMP-9 genes polymorphism on the development of early AMD. This study proved that the frequency of the MMP-2 (-735) C/T and MMP-3 (-1171) 5A/6A genotypes did not differ significantly between the patients with early AMD and the control group, while the MMP-9 (-1562) C/C genotype was more frequently detected in patients with AMD than the control group (73.7% vs. 64.6%, P = 0.048) (Liutkeviciene et al, 2013). The logistic regression analysis showed that the MMP-9 (-1562) C/C genotype increased the likelihood to develop early AMD (OR = 1.51, 95% CI: 1.01-2.21; P = 0.046).…”
Section: Matrix Metalloproteinases (Mmp-2 -3 and -9) Association Witmentioning
confidence: 75%
See 1 more Smart Citation
“…To our knowledge, there is only one study analyzing the impact of MMP-2, MMP-3, and MMP-9 genes polymorphism on the development of early AMD. This study proved that the frequency of the MMP-2 (-735) C/T and MMP-3 (-1171) 5A/6A genotypes did not differ significantly between the patients with early AMD and the control group, while the MMP-9 (-1562) C/C genotype was more frequently detected in patients with AMD than the control group (73.7% vs. 64.6%, P = 0.048) (Liutkeviciene et al, 2013). The logistic regression analysis showed that the MMP-9 (-1562) C/C genotype increased the likelihood to develop early AMD (OR = 1.51, 95% CI: 1.01-2.21; P = 0.046).…”
Section: Matrix Metalloproteinases (Mmp-2 -3 and -9) Association Witmentioning
confidence: 75%
“…An allele of MMP-2 rs2287074 was less prevalent in subjects with late AMD than in those with early or no AMD (p = 0.01) (Seitzman et al, 2008). The third study also proved that analysis of MMP-2 (-1306 C/T) gene polymorphism has not revealed any differences in the genotype distribution between patients with early AMD and reference group subjects when analyzed in overall group, but MMP-2 gene C/C genotype was more frequent in AMD patients younger than 65 years comparing to AMD group ≥65 years (67.21% vs. 49.37%, p = 0.039), and C/T genotype was more frequent in AMD patients ≥65 years comparing to AMD patients <65 years (26.23% vs. 44.3%, p = 0.033) (Liutkeviciene et al, 2013). MMP-2 expression in experimental models (Berglin et al, 2003) and in Bruch's membrane-choroid prepara tions in human donor eyes with AMD diagnosis were also analyzed (Hussain et ., 1998).…”
Section: Expression Of Matrix Metalloproteinases In Hu Man Retina Andmentioning
confidence: 99%
“…Эти данные подтверждаются и резуль-татами исследования в нашей группе пациентов. Единичные работы, посвященные исследованию полиморфизма MMP и TNFα у пациентов с ВМД, показывают отсутствие прямой ассоциирован-ности полиморфизма этих генов с развитием заболевания [7,24,27,35]. Из единичных поли-морфных позиций только для TNFα-308 пока-зана ассоциированность с патологией в нашей группе пациентов, что может быть связано как с популяционными особенностями, так и со слож-ностью патогенетических механизмов развития заболевания [4].…”
Section: примечание or -отношение шансов Or 95%ci -доверительный инunclassified
“…Ortak H. предположил, что MMP2 C-1306T промоторный полиморфизм вряд ли играет существенную роль в риске развития ВМД [ 27]. В то же время есть данные, что частота CC и CT генотипов выше у пациентов с ВМД мо-ложе 65 лет, чем у здоровых [25]. Можно предпо-ложить, что ассоциированность сложных геноти-пов с высокими значениями отношения шансов развития ВМД реализуется именно за счет сете-вого синергизма, несмотря на то, что в качестве мономаркеров в различных исследованиях роль этих полиморфных позиций сомнительна.…”
Section: примечание or -отношение шансов Or 95%ci -доверительный инunclassified
See 1 more Smart Citation